Which dialysis modality offers better quality of life for chronic kidney disease patients: CAPD or hemodialysis (HD)? a scoping review - S. Ningsih, Hesti; Khoiriyati, Azizah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
In advanced stages of chronic kidney disease (CKD), where kidney function has severely declined, renal replacement therapy becomes essential. This scoping review aims to compare the impact of two common dialysis modalities—hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD)—on various aspects of patients' quality of life, including physical, emotional, and social dimensions. This review was conducted using the Population and Concept (PC) framework, which is commonly applied in scoping reviews, and followed the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines for reporting. A comprehensive literature search was performed across four databases: PubMed, ProQuest, ScienceDirect, and Google Scholar. The search focused on full-text, English-language articles published within the last ten years. Inclusion criteria included studies involving adult CKD patients undergoing HD or CAPD with quality of life as the primary outcome. Studies were excluded if they involved pediatric populations, case reports, or were not peer-reviewed. Nineteen studies met the eligibility criteria and were included in this review. The findings suggest that CAPD therapy is potentially associated with better physical quality of life compared to HD. However, results regarding emotional and social aspects were mixed, with some studies indicating comparable outcomes between modalities, while others showed conflicting results. Further research is warranted, particularly regarding emotional well-being and social support in CAPD patients. While CAPD may offer certain advantages in physical quality of life, comprehensive comparisons across emotional and social domains remain inconclusive. Limitations of this review include the small number of eligible studies, variation in study designs, and heterogeneity in patient populations. These limitations highlight the need for more robust and standardized research in this area.